(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
As a result of the collapse of the state of Nadirshahs in Iran (1747), a new state of Afghanistan was formed, which in the 19th century became a sphere of interaction of interests of capitalistically developed England. The growth of capitalism in Russia ended with the establishment of the Turkestan Governorate General in the Central Asian khanates. This article analyzes the historical sources of the life and work of Ishaq Khan in Samarkand.